Tooth extraction complication and treatments at the Exodontia Clinic of the Oral and Dental Hospital of the Faculty of Dentistry of Universitas Padjadjaran Bandung - Wirastriajeng, Harnastiti; Riawan, Lucky; Syamsudin, Endang (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2007)
The patientâs dental conditions who visited the Exodontia Clinic of the Oral and Dental Hospital of the Faculty of Dentistry of Padjadjaran University, Bandung, were generally in a severe damage stage, causing problems in extraction. This condition, as well as the operator âs (co-assistant student) that still have limited capability, Â may increase the risk of complication. This study was conducted at the Exodontia Clinic of the Oral and Dental Hospital of the Faculty of Dentistry of Padjadjaran University. It is conducted from March 13 to May 13, 2007. It is aimed at finding out the types of tooth extraction complications including the treatments towards the problems. This study was a prospective descriptive using the survey method. The study showed that there were 70 cases (64% ) of complications occurred, namely, 37 cases (6.68%) in the maxilla, and 33 cases (5.96% ) in the mandible. The complications that occurred consisted of root fracture (41 .43%), crown fracture (32.86% ), soft tissue laceration (14 .29%), maxillary sinus perforations (2.86% ), syncope (2.86% ), swelling (2.86% ), and secondary hemorrhage (2.86% ).